2016
DOI: 10.18203/2394-6040.ijcmph20162890
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of universal precautions among nursing staff at a tertiary care hospital in South Gujarat, India

Abstract: Background: Health care providers are at an increased risk of exposure to various infections like HIV, Hepatitis B, Hepatitis C etc. These infections are prevented if proper universal precautions are observed by health care providers consistently in their day to day clinical work. In study we have explored knowledge and practice of universal precautions among nursing staff. Methods: A cross sectional study carried out among staff nurses in December 2013. Self-administered semi structured proforma was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
1
14
3
Order By: Relevance
“…The present study found that, less than only one quarter of nurses and physicians were using the personal protective barrier during contact with infectious patient or blood with non statistical significant differences were found. This result was inconsistent with finding obtained from (Solanky et al 2016& Abu Salam et al2017) studies who found that, about one hundred percent of HCPs used personal protective measures such as gloves, gown, cap and face masks in day to day practice during dealing with blood or body fluids of the patients. As regard to the use needles-cutter or specific container for proper discarding of the used syringes and other sharp equipment, the study revealed that about two-thirds of the nurses and doctors dispose the sharp items and used syringes into puncture-proof container at point of use with statistical significant difference was found between the two groups, this finding was inconsistent with (Peethala and Garapati, 2017) who reported that proper disposal of used sharps items and needles were not in practices of most participants.…”
Section: Part Ii: Regarding To Personal Hygiene and Safety Practice Acontrasting
confidence: 67%
See 1 more Smart Citation
“…The present study found that, less than only one quarter of nurses and physicians were using the personal protective barrier during contact with infectious patient or blood with non statistical significant differences were found. This result was inconsistent with finding obtained from (Solanky et al 2016& Abu Salam et al2017) studies who found that, about one hundred percent of HCPs used personal protective measures such as gloves, gown, cap and face masks in day to day practice during dealing with blood or body fluids of the patients. As regard to the use needles-cutter or specific container for proper discarding of the used syringes and other sharp equipment, the study revealed that about two-thirds of the nurses and doctors dispose the sharp items and used syringes into puncture-proof container at point of use with statistical significant difference was found between the two groups, this finding was inconsistent with (Peethala and Garapati, 2017) who reported that proper disposal of used sharps items and needles were not in practices of most participants.…”
Section: Part Ii: Regarding To Personal Hygiene and Safety Practice Acontrasting
confidence: 67%
“…This finding coincides with Amoran & Onwube, (2013) who mentioned that unavailability of infection control equipment consider the major factor for non-adherence with UPs among HCPs. Solanky et al (2016) and Afolaranmi et al(2017) stated that proper and mandatory training must be regularly provided to HCPs to develop and refresh their knowledge about SPs. Training should includes hand washing, use of various protective barriers, prevention and managing of needles prick injury and proper handling of hazards waste.…”
Section: Part Iv: Relation Between Levels Of Personal Hygiene Practicmentioning
confidence: 99%
“…Only 44.3% nurses mentioned all the correct measures for universal precautions. 9 Auxiliary nurse midwives (ANMs) are the main service providers at the sub-centre level. Sub-centres are the peripheral most formal health care delivery facilities and first formal contact point of the health system with the community.…”
Section: Introductionmentioning
confidence: 99%
“…These infections are prevented if proper standard precautions which encompasses a wide range of steps are observed by health care providers consistently in their day to day clinical work to reduce the risk of exposure to blood and body fluids to protect self, patients and co-workers from infections. [4][5][6][7][8][9][10][11][12][13][14] In order to protect from the infections there are four important practices recommended in standard precaution are hand washing, use of protective barriers to prevent direct contact, safe handling and disposal of sharps and safe decontamination of instruments and other contaminated instruments. 6 Studies done previously reported that nurses are the commonest health care providers who are being exposed to infection.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] In order to protect from the infections there are four important practices recommended in standard precaution are hand washing, use of protective barriers to prevent direct contact, safe handling and disposal of sharps and safe decontamination of instruments and other contaminated instruments. 6 Studies done previously reported that nurses are the commonest health care providers who are being exposed to infection. 8,11 Therefore, the present study was undertaken with the objectives, to assess the knowledge and practices of nursing staff regarding standard precautions.…”
mentioning
confidence: 99%